Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Answer:
6 = x
Step-by-step explanation:
first, we simplify the parenthesis by distributing the 4
3 = 4(x - 2) + 5 - 3x
3 = 4x - 8 + 5 - 3x
then, you add like terms
3 = x - 3
then add 3 to both sides to isolate x
6 = x
Answer:
x = 6
Step-by-step explanation:
multiply both terms in the parenthesis by the factor 4:
3 = 4(x-2) + 5 - 3x
3 = (4*x) - (4*2) + 5 - 3x
then simplify
3 = 4x - 8 + 5 - 3x
rearrange terms
3 = 4x - 3x - 8 + 5
subtract 3x from 4x: (4x - 3x = 1x, which is just x)
3 = 1x - 3
3 = x - 3
then add 3 to both sides:
6 = x
x = 6
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.